The Effectiveness of Using the Zoom Application as an Online Learning Media for Post-Pandemic Karawang Campus Students - Yeny Rostiani; Lila Setiyani; Tania Octaviani (PT ARRUS Intelektual Indonesia, 2023)
The learning process carried out online after the pandemic is something that needs to be studied and also evaluated, considering that during the pandemic there are obstacles during the learning process. The purpose of this study is to see an overview of the effectiveness of using the Zoom application after the pandemic. This research is qualitative research using the Grounded Theory method. The resource persons in this study amounted to 26 people consisting of students around the campus in Karawang. The data validation technique in this study uses source triangulation which is done by checking data from several sources but with different techniques. Based on the results of the study, it was found that 85% liked face-to-face learning, because face-to-face learning was more communicative, the learning process was more effective. And 58% prefer the Zoom application as the most effective Online learning medium compared to other applications